GAMBARAN PERILAKU SEKSUAL PRANIKAH PADA MAHASISWA ALUMNI PESANTREN DI PROVINSI DKI JAKARTA - Zulfaa Nurin Nuhaa; Aditya Kusumawati; Syamsulhuda Budi Musthofa (Jurnal Kesehatan Masyarakat (Undip), 2021)
Premarital sexual behavior among adolescents is an increasing problem, especially in big cities such as Jakarta. This problem also occurs to many college students in the late adolescence stage. Premarital sexual behavior can negatively impact health and non-health aspects. This problem encouraged the parents to send their children to Islamic boarding school, hoping a good character could be developed, averting such behavior. The data on this qualitative descriptive research was collected by an indepth interview with eight research subjects with the snowball sampling method. The validity test was done by nine triangulation subjects who are close friends of research subjects at this moment and when they were on Islamic boarding school, while the reliability test was done by data auditing. In this study, the research subjects were labeled as a delinquent by their parents, thus forced to go to modern Islamic boarding school hoping a good character as the earlier alumni while having excellent general knowledge. Still, that label was planted in themselves, and their character was not as expected, which made them feel accustomed doing a deviant behavior such as premarital sex.